Hepatoblastoma in children aged less than six months at diagnosis: A report from the SIOPEL group. Issue 1 (18th September 2017) - Dall'Igna, Patrizia; Brugieres, Laurence; Christin, Anne Sanlaville; Maibach, Rudolf; Casanova, Michela; Alaggio, Rita; de Goyet, Jean de Ville; Zsiros, Jozsef; Morland, Bruce; Czauderna, Piotr; Childs, Margaret; Aronson, Daniel C.; et al.
Abstract: Background: The purpose of this study was to evaluate clinical characteristics, treatment, and survival of children, who were diagnosed with hepatoblastoma (HB) in their first 6 months of age, enrolled in the SIOPEL 2 and 3 protocols. Methods: Seventy‐nine patients, treated between 1994 and 2006, were analyzed after stratification into three age groups: <1 month, between 1 and 3 months, and between 3 and 6 months. All received preoperative chemotherapy. Results: Clinical characteristics were similar in both trials: 4 patients had pulmonary metastases at diagnosis, 4 had α‐fetoprotein <100 ng/ml, 68 were operated by partial hepatectomy, and 7 received liver transplant. Chemotherapy courses were delayed in 8.5%, 8.4%, and 11.8% of cycles in the three groups. Doses were calculated according to weight for children <5 and 5–10 kg, and further reduced in 18.1%, 6.8%, and 5.9% of cycles. Acute toxicity was manageable. Long‐term hearing loss was the major problem at follow‐up occurring in two‐thirds of children. Ten patients experienced progression or relapse, and 5 of 10 died. After a median follow‐up of 5.6 years, the 5‐year overall survival (OS) and event‐free survival (EFS) were 91% (95% confidence interval [CI]: 84–96%) and 87% (95% CI: 78–92%), respectively. Conclusions: The 5‐year OS and EFS of children <6 months of age affected by HB seem to be similar to those documented in the elder children. Dose reduction does not seem to jeopardize the long‐term outcome and may explain the lower toxicity profile. Ototoxicity though appears as high as in the whole population of SIOPEL 2 and 3. The treatment for these children should be further explored in international studies, particularly focusing on prevention of hearing loss.